The myth of post-reform income stagnation in Brazil - Carvalho Filho, Irineu de; Chamon, Marcos (IMF working paper ;, 2006)
This paper uses Engel curves to estimate real income growth in Brazil. The estimated per capita household real income growth in metropolitan areas during 1987-2002 is about 4 1/2 percent per year, well above the "headline" growth of 1 1/2 percent obtained by deflating nominal incomes by the CPI. This suggests a substantial CPI bias during that period, likely owing to one-off effects of trade liberalization and inflation stabilization. The estimated unmeasured gains are higher for poorer households, implying a marked reduction in "real" inequality. This finding challenges the conventional wisdom that post-reform real income growth in Brazil was low.